2019
DOI: 10.3390/ma12091475
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Predicting and Classifying the Tensile Strength of Polymeric Films Fabricated via Different Production Processes

Abstract: In this study, machine learning algorithms (MLA) were employed to predict and classify the tensile strength of polymeric films of different compositions as a function of processing conditions. Two film production techniques were investigated, namely compression molding and extrusion-blow molding. Multi-factor experiments were designed with corresponding parameters. A tensile test was conducted on samples and the tensile strength was recorded. Predictive and classification models from nine MLA were developed. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 31 publications
0
22
0
2
Order By: Relevance
“…A correlation between the interphase properties of the composite and its reinforcement was also established. Altarazi et al [334] fabricated polymer composites using two different techniques namely, compression moulding and extrusion blow moulding. They used nine ML algorithms to predict the flexure strength of the composites as a function of material composition and manufacturing conditions.…”
Section: Support Vector Machines (Svm)mentioning
confidence: 99%
“…A correlation between the interphase properties of the composite and its reinforcement was also established. Altarazi et al [334] fabricated polymer composites using two different techniques namely, compression moulding and extrusion blow moulding. They used nine ML algorithms to predict the flexure strength of the composites as a function of material composition and manufacturing conditions.…”
Section: Support Vector Machines (Svm)mentioning
confidence: 99%
“…Altarazi et al applied multiple algorithms at a time to predict and classify tensile strength of polymeric films of different compositions. The used algorithms were stochastic gradient descent (SGD), ANN, k-nearest neighbors (kNN), decision tree (DT), regression analysis, SVM, random forest (RF), logistic regression (LoR) and AdaBoost (AB) [ 93 ]. Experimental results demonstrated that SVM algorithm showed better prediction results.…”
Section: Classification Based On Textile Processesmentioning
confidence: 99%
“…However, ANFIS showed better performance with small datasets. Altarazi et al used multiple algorithms i.e., stochastic gradient descent (SGD), ANN, k-nearest neighbors (kNN), decision tree (DT), regression analysis, support vector machine (SVM), random forest (RF), logistic regression (LoR) and AdaBoost (AB), for the prediction and classification of tensile strength of polymeric films with various compositions [ 24 ]. The obtained results show that SVM algorithm has superior predictive ability.…”
Section: Introductionmentioning
confidence: 99%